Governing Australia’s Dairy Farm Workforce: A New Terrain for Negotiating Rural Community Sustainability - Santhanam-Martin, Michael; Nettle, Ruth (The International Journal of Sociology of Agriculture and Food, 2014)
Amidst heightened policy interest in the future of agriculture, there is an emerging new focus on the topic of the farm workforce in Australia. Will agricultural industries have the people – both farm business owners and employees – that they need? While government and industry are focused on the sustainability of production, farm workforce dynamics also intersect with wider economic and social processes in rural communities, an issue of ongoing concern for rural studies scholars. Here we examine currently emerging policy and action on farm workforce issues from a governance perspective, using the dairy industry in the Australian state of Victoria as a case study. Drawing on both governmentality and political science approaches, we explore workforce governance through three overlapping studies: policy-making, farmers’ lived experiences and industry-led collective action. Across the three studies we ask, first, what is revealed about neo-liberal agricultural industry governance and, second, what possibilities the new focus on workforce creates for rural communities concerned about social and economic sustainability. We argue that the farm workforce as a policy object crystallizes the tension between the strongly individualizing discourse of neo-liberalism and the pursuit of public policy objectives framed at the collective scale. If the neo-liberalizing project is understood as a work in progress, then the issue of the farm workforce can be seen as another dilemma to be worked through. In this the roles of collective agents and spaces in both agricultural industries and in communities are critical, making the farm workforce a terrain for innovation in which rural communities can negotiate their interests afresh.